The role of virulence factors inCandida albicanspathogenicity - Tri Wibawa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Candida albicans is a classical example of causative agent for opportunistic fungalinfection. Normally, it colonizes skin, gastrointestinal tract, genital, and mucosalmembranes, but in certain condition it may responsible for diseases. This phenomenonwas mainly associated with immunological status of the host. However, there werefindings that showed the possibility of putative virulence factors work on the transitionof commensally to pathogenic role of the yeast. In this review, some virulence factorswere discussed. Indeed, there were factors that may be considered as putative virulencefactors of C. albicans.